Micron layered rare earth-based denitration catalyst as well as preparation method and application thereof

By preparing micron-layered rare earth-based denitrification catalysts, the problems of easy deactivation and anti-poisoning of low-temperature denitrification catalysts in non-electric industries have been solved, and efficient and stable flue gas denitrification effects have been achieved. It is suitable for steel sintering, dry cement and chemical industries.

CN120644210APending Publication Date: 2025-09-16NANJING TECH UNIV +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510758079.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-09
Publication Date
2025-09-16

AI Technical Summary

Technical Problem

Existing low-temperature denitrification catalysts are easily deactivated due to clogging with ammonium bisulfate in non-power industry applications, and their resistance to water-sulfur poisoning is insufficient, making them unable to be effectively applied to the high-humidity and high-sulfur flue gas environment of the non-power industry.

Method used

A micron-layered rare earth-based denitrification catalyst is used, with micron-layered titanium dioxide as the carrier and a composite oxide of cerium oxide and copper oxide as the active component. It is prepared by proton exchange freezing method and impregnation method, and the layered structure is used to enhance the stability of the catalyst and its resistance to sulfur poisoning.

Benefits of technology

The denitrification efficiency is higher than 90% in the temperature range of 120-240℃, and there is no significant change in efficiency after using it at 180℃ for 24 hours. It has excellent low-temperature denitrification and resistance to water-sulfur poisoning, is environmentally friendly and cost-effective.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120644210A_ABST
    Figure CN120644210A_ABST
Patent Text Reader

Abstract

The invention discloses a micron layered rare earth based denitration catalyst as well as a preparation method and application thereof. The catalyst takes micron layered titanium dioxide as a carrier and a composite oxide of cerium oxide and copper oxide as an active component. The catalyst synthesized by the method has the advantages of high low-temperature activity, large specific surface area, high active site exposure ratio, strong poisoning resistance and the like, and can realize the target of low-temperature denitration of complex flue gas in non-electric industries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a micron layered rare earth-based denitration catalyst and a preparation method and application thereof, belonging to the field of air pollution control. Background Art

[0002] International regulations such as the EU Industrial Emissions Directive (IED) have also put forward similar requirements for non-electricity industries. On the other hand, non-electricity industries contribute more than 70% of the country's NO x , among which NO in the steel sintering process x Emissions from the steel industry account for over 50% of the total. Flue gas temperatures in non-electric industries like steel are typically 200°C, sometimes even below 180°C, with moisture contents ranging from 7% to 15%. Traditional SCR catalysts are easily blocked and deactivated by ammonium bisulfate (ABS), leading to an urgent need for the development of low-temperature, high-efficiency flue gas denitrification catalysts.

[0003] At present, researchers have developed a series of low-temperature denitrification catalysts: (1) manganese-based catalysts, which can achieve a denitrification efficiency of more than 90% at 160°C. However, manganese-based denitrification catalysts have weak resistance to water and sulfur poisoning. Manganese oxide is easy to precipitate gradually under high water content. At the same time, it will react with SO3 to form sulfate when the sulfur content is high, resulting in permanent deactivation of the catalyst. Therefore, it can only be used for low-temperature denitrification in a sulfur-free environment; (2) molecular sieve catalysts, which have high activity in a wide temperature range of 200-400°C and strong resistance to water and sulfur poisoning, but they are not very effective at 20 The activity in the temperature range below 0℃ is relatively low, and it can only be applied to flue gas denitrification in some non-electric industries; (3) High vanadium-based catalysts. Vanadium-based catalysts have excellent denitrification performance at medium and high temperatures. In the low-temperature field of non-electric industries, the low-temperature activity can be improved by increasing the vanadium oxide content. However, this will cause two problems. First, the higher the vanadium oxide content, the higher the SO2 / SO3 oxidation rate, which will lead to physical coverage of ammonium bisulfate and physical deactivation of the catalyst. Second, vanadium oxide has certain biological toxicity. After the vanadium-based denitrification catalyst is deactivated, it will cause secondary environmental pollution. Therefore, the development of low-temperature, high-efficiency and environmentally friendly denitrification catalysts that can be used in the non-electric industry is one of the current research focuses. Summary of the Invention

[0004] The purpose of the present invention is to address the current status and problems of simultaneous denitration in non-electric industries and to propose a micron layered rare earth-based denitration catalyst and its preparation method and application.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A micron-layered rare earth-based denitration catalyst uses micron-layered titanium dioxide as a carrier and a composite oxide of cerium oxide and copper oxide as an active component. The catalyst is prepared by a proton exchange freezing method-impregnation method. The mass percentage of the active component is 1-50% based on the mass of the carrier, and the mass ratio of cerium oxide to copper oxide in the active component is 1:(0.1-5).

[0007] Furthermore, based on the mass of the carrier, the mass percentage of the active component is 5-30%, and the mass ratio of cerium oxide to copper oxide in the active component is 1:(0.1-1).

[0008] A method for preparing the above catalyst is as follows:

[0009] (1) Preparation of micron-layered titanium dioxide by proton exchange freezing method

[0010] Preparation of layered K2Ti4O9 powder: titanium source and potassium source are mixed evenly, then placed in a microwave sintering furnace for microwave heating, and layered K2Ti4O9 powder is obtained after washing and drying;

[0011] Preparation of slurry: Layered K2Ti4O9 powder and deionized water are mixed uniformly, and K2Ti4O9 colloid is obtained after ultrasonic dispersion. Nitric acid is then added and stirred continuously, and proton exchange is carried out. After filtration, H2Ti4O9 is obtained. H2Ti4O9, a binder, and deionized water are then mixed uniformly to obtain a slurry.

[0012] Preparation of micron layered titanium dioxide: The slurry is first placed in liquid nitrogen and frozen for 30 to 60 minutes, then vacuum dried, and finally calcined at high temperature to obtain micron layered titanium dioxide;

[0013] (2) Preparation of catalyst by impregnation method

[0014] Weigh cerium salt, copper salt and deionized water and mix them evenly to prepare a precursor mixed solution, then place the micron layered titanium dioxide prepared in step (1) into the precursor mixed solution, vacuum dry and then calcine at high temperature to obtain a catalyst.

[0015] In the technical solution of the present invention: the preparation conditions of the layered K2Ti4O9 powder in step (1) are as follows:

[0016] The titanium source is anatase titanium dioxide, the potassium source is potassium hydroxide, and the molar ratio of the titanium source to the potassium source is 1-3:1; the microwave heating power is 1.0-2.0 kW, the heating time is 2-4 hours; the drying temperature is 80-100° C., and the drying time is 4-8 hours.

[0017] In the technical solution of the present invention: the preparation conditions of the slurry in step (1) are as follows:

[0018] The power of ultrasonic dispersion is 400-600W, and the time of ultrasonic dispersion is 4-6h;

[0019] The concentration of nitric acid is 0.5 to 2 mol / L, the mass ratio of layered K2Ti4O9 powder to nitric acid is 1:(5 to 10), and the proton exchange time is 12 to 36 hours.

[0020] The binder is chitosan, and the mass ratio of H2Ti4O9 to the binder is 1:(2-3).

[0021] In the technical solution of the present invention: the conditions for preparing micron-layered titanium dioxide in step (1) are as follows: the vacuum drying temperature is 20-40°C, and the vacuum drying time is 24-48 hours; the high-temperature calcination temperature is 400-600°C, and the high-temperature calcination time is 4-8 hours.

[0022] In the technical solution of the present invention: in step (2), the cerium salt is cerium nitrate hexahydrate or cerium chloride, and the copper salt is copper nitrate or copper chloride;

[0023] The temperature of vacuum drying is 20-40° C., and the time of vacuum drying is 12-24 hours; the temperature of high-temperature roasting is 500-600° C., and the time of high-temperature roasting is 2-4 hours.

[0024] In the technical solution of the present invention, the catalyst is used in the denitrification of complex flue gases in non-electricity industries.

[0025] Furthermore, non-electric industries include steel sintering, dry cement and chemical industries.

[0026] The catalyst activity evaluation experimental conditions of the present invention are as follows: 1 mL of a 20-40 mesh catalyst is poured into a 6 mm inner diameter quartz tube, secured with quartz wool and wire mesh, and placed in a tube furnace. The actual temperature of the catalytic reaction is adjusted by controlling the heating temperature of the tube furnace. The inlet gas components are NO (500 ppm), NH3 (500 ppm), O2 (11 vol.%), H2O (5 vol.%), SO2 (200 ppm), and the remainder is N2. The total gas flow rate is 500 mL / min. The temperature is controlled at 120-240°C, and the temperature is stabilized at 30°C for 30 minutes at intervals. The NO concentration is measured using a flue gas analyzer. The catalyst denitrification efficiency is greater than 90% within the temperature range of 180-240°C, and the denitrification efficiency does not change significantly after the catalyst is used at 180°C for 24 hours.

[0027] Beneficial effects:

[0028] (1) The present invention first uses microwave heating of titanium source and potassium source to prepare K2Ti4O9 powder with a layered structure, then dissolves K2Ti4O9 in water to form a colloid, and then uses nitric acid and K2Ti4O9 colloid to produce proton exchange to form H2Ti4O9 with a layered structure. In order to prevent H2Ti4O9 from decomposing and agglomerating during the roasting process to cause structural damage, the present invention uses a binder chitosan to increase the absolute value of the Zeta potential of H2Ti4O9, thereby enhancing its stability. Then, liquid nitrogen freezing is used to induce ice crystal growth. The binder can interact with the ice crystal interface to limit the lateral expansion of the ice crystal, thereby inducing the ice crystal to grow in a directional manner along the temperature gradient to form a layered arrangement, and can also resist the capillary stress generated by the sublimation of the ice crystal to avoid the collapse of the layered structure. Finally, the evenly dispersed H2Ti4O9 is decomposed by high-temperature roasting to obtain micron-layered titanium dioxide;

[0029] (2) In the present invention, a catalyst is obtained by immersing a micron layer of titanium dioxide in a precursor mixture formed by a cerium salt and a copper salt, and then calcining the mixture at a high temperature; wherein cerium oxide and copper oxide can form a solid solution, further enhancing the redox performance of the active components, and can also allow cerium oxide and copper oxide to enter the interior of the layered titanium dioxide, avoiding the active sites existing only on the outer surface, thereby obtaining a uniformly loaded catalyst;

[0030] (3) The present invention uses micron layered titanium dioxide as a carrier, which has a high surface roughness, can increase the contact angle, reduce the adsorption of water molecules on the catalyst surface, and at the same time, the multi-level pores of the layered structure can accelerate the diffusion and overflow of water molecules; in addition, the oxygen vacancies in the layered titanium dioxide can preferentially adsorb SO2 and convert it into reversible sulfate / sulfite, thereby avoiding the reaction of active sites with SO2 and enhancing the sulfur poisoning resistance of the catalyst; finally, because the layered structure provides abundant surface steps and edge sites, the dispersion of active components can be increased, thereby increasing the active site density per unit area of ​​the catalyst, and enhancing the redox ability through interfacial charge transfer, ultimately enhancing the denitrification activity of the catalyst;

[0031] Therefore, the catalyst prepared by the present invention not only has excellent low-temperature denitrification performance, but also has excellent resistance to water-sulfur poisoning. In addition, the catalyst component is environmentally friendly, cost-effective, and has strong application and promotion value. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 、 2 This is the SEM image of the catalyst prepared in Example 1;

[0033] Figure 2 This is a graph of the denitration efficiency of the catalysts prepared in Examples 1-3 and Comparative Example 1;

[0034] Figure 3 This is a graph of the denitration efficiency of the catalysts prepared in Examples 1-3 and Comparative Example 1; Figure 4 This is a graph showing the 24h denitrification efficiency of the catalysts prepared in Examples 1-3 and Comparative Example 1. DETAILED DESCRIPTION

[0035] The present invention will be further described below with reference to the following examples. The examples are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operating processes. However, the protection scope of the present invention is not limited to the following examples.

[0036] Example 1

[0037] (1) Preparation of micron-layered titanium dioxide by proton exchange freezing method

[0038] 5 g of anatase titanium dioxide and 3.13 g of potassium hydroxide were weighed and mixed evenly, and then placed in a microwave sintering furnace for microwave heating (power of 1 kW, heating time of 4 h). After washing and drying (drying temperature of 80 ° C, drying time of 8 h), layered K2Ti4O9 powder was obtained. Then 2 g of layered K2Ti4O9 powder and 80 g of deionized water were weighed and mixed evenly. After ultrasonic dispersion at 400 W power for 4 h, K2Ti2O9 colloid was obtained. Then 10 g of 0.5 mol / L nitric acid was added and the mixture was stirred for 2 hours. Stirring continuously at a rate of 200 r / min to ensure proton exchange for 24 hours, and then filtering to obtain H2Ti4O9, and then evenly mixing 1g of H2Ti4O9, 2g of chitosan, and 50g of deionized water to obtain a slurry, which is then placed in a copper cup and occupies 50% of its capacity. The copper cup is then placed in liquid nitrogen and the liquid nitrogen level is maintained at 20% of the outer surface of the copper cup. After freezing for 30 minutes, the copper cup is placed in a vacuum drying oven at 20°C for 24 hours, and finally calcined at 400°C for 4 hours to obtain micron-layered titanium dioxide;

[0039] (2) Preparation of catalyst by impregnation method

[0040] 2 g of cerium nitrate hexahydrate, 0.13 g of copper nitrate, and 120 g of deionized water were weighed and mixed uniformly to prepare a precursor mixed solution. The micron layered titanium dioxide prepared in step (1) was then placed in the precursor mixed solution, vacuum dried at 20° C. for 12 h, and then calcined at 500° C. for 2 h to obtain a catalyst.

[0041] (3) Catalytic activity test

[0042] 1 mL of a 20-40 mesh catalyst was poured into a 6 mm inner diameter quartz tube, secured with quartz wool and wire mesh, and placed in a tube furnace. The actual temperature of the catalytic reaction was adjusted by controlling the heating temperature of the tube furnace. The inlet gas components were: NO (500 ppm), NH3 (500 ppm), O2 (11 vol.%), H2O (5 vol.%), SO2 (200 ppm), and the remainder was N2. The total gas flow rate was 500 mL / min, and the temperature was controlled at 120-240°C. The temperature was stabilized at 30°C for 30 minutes each. The NO concentration was measured using a flue gas analyzer. The denitrification efficiency of the catalyst was higher than 90% within the temperature range of 180-240°C, and there was no significant change in the denitrification efficiency after the catalyst was used at 180°C for 24 hours.

[0043] Example 2

[0044] (1) Preparation of micron-layered titanium dioxide by proton exchange freezing method

[0045] 5 g of anatase titanium dioxide and 3.13 g of potassium hydroxide were weighed and mixed evenly, and then placed in a microwave sintering furnace for microwave heating (power of 1.5 kW, heating time of 3 h), and after washing and drying (drying temperature of 90 ° C, drying time of 6 h) to obtain layered K2Ti4O9 powder. Then 2 g of layered K2Ti4O9 powder and 120 g of deionized water were weighed and mixed evenly, and ultrasonically dispersed at a power of 500 W for 5 h to obtain K2Ti4O9 colloid. Then 16 g of nitric acid with a concentration of 1 mol / L was added and Stirring continuously at a rate of 300 r / min to ensure proton exchange for 24 hours, and then filtering to obtain H2Ti4O9, and then evenly mixing 1g of H2Ti4O9, 3g of chitosan, and 70g of deionized water to obtain a slurry, which is then placed in a copper cup and occupies 60% of its capacity. The copper cup is then placed in liquid nitrogen and the liquid nitrogen level is maintained at 25% of the outer surface of the copper cup. After freezing for 50 minutes, the copper cup is placed in a vacuum drying oven at 30°C for 36 hours, and finally calcined at 500°C for 6 hours to obtain micron-layered titanium dioxide;

[0046] (2) Preparation of catalyst by impregnation method

[0047] 2 g of cerium chloride, 1.12 g of copper nitrate, and 140 g of deionized water were weighed and mixed uniformly to prepare a precursor mixed solution. The micron layered titanium dioxide prepared in step (1) was then placed in the precursor mixed solution, vacuum dried at 30° C. for 18 h, and then calcined at 600° C. for 3 h to obtain a catalyst.

[0048] (3) Catalytic activity test

[0049] 1 mL of a 20-40 mesh catalyst was poured into a 6 mm inner diameter quartz tube, secured with quartz wool and wire mesh, and placed in a tube furnace. The actual temperature of the catalytic reaction was adjusted by controlling the heating temperature of the tube furnace. The inlet gas components were: NO (500 ppm), NH3 (500 ppm), O2 (11 vol.%), H2O (5 vol.%), SO2 (200 ppm), and the remainder was N2. The total gas flow rate was 500 mL / min, and the temperature was controlled at 120-240°C. The temperature was stabilized at 30°C for 30 minutes each. The NO concentration was measured using a flue gas analyzer. The denitrification efficiency of the catalyst was higher than 90% within the temperature range of 180-240°C, and there was no significant change in the denitrification efficiency after the catalyst was used at 180°C for 24 hours.

[0050] Example 3

[0051] (1) Preparation of micron-layered titanium dioxide by proton exchange freezing method

[0052] 5 g of anatase titanium dioxide and 3.13 g of potassium hydroxide were weighed and mixed evenly, and then placed in a microwave sintering furnace for microwave heating (power of 2 kW, heating time of 2 h). After washing and drying (drying temperature of 100 ° C, drying time of 4 h), layered K2Ti4O9 powder was obtained. Then 2 g of layered K2Ti4O9 powder and 160 g of deionized water were weighed and mixed evenly. After ultrasonic dispersion at 600 W power for 6 h, K2Ti4O9 colloid was obtained. Then 20 g of 2 mol / L nitric acid was added and the mixture was stirred for 2 hours. Stirring continuously at a rate of 400 r / min to ensure proton exchange for 36 hours, and then filtering to obtain H2Ti4O9. Then, 1g of H2Ti4O9, 3g of chitosan, and 100g of deionized water were evenly mixed to obtain a slurry. The slurry was then placed in a copper cup and occupied 80% of its capacity. The copper cup was then placed in liquid nitrogen and the liquid nitrogen level was maintained at 30% of the outer surface of the copper cup. After freezing for 60 minutes, the copper cup was placed in a vacuum drying oven at 40°C for 48 hours, and finally calcined at 600°C for 8 hours to obtain micron-layered titanium dioxide.

[0053] (2) Preparation of catalyst by impregnation method

[0054] 2 g of cerium chloride, 2.36 g of copper chloride, and 160 g of deionized water were weighed and mixed evenly to prepare a precursor mixed solution. The micron layered titanium dioxide prepared in step (1) was then placed in the precursor mixed solution, vacuum dried at 40° C. for 24 h, and then calcined at 600° C. for 4 h to obtain a catalyst.

[0055] (3) Catalytic activity test

[0056] 1 mL of a 20-40 mesh catalyst was poured into a 6 mm inner diameter quartz tube, secured with quartz wool and wire mesh, and placed in a tube furnace. The actual temperature of the catalytic reaction was adjusted by controlling the heating temperature of the tube furnace. The inlet gas components were: NO (500 ppm), NH3 (500 ppm), O2 (11 vol.%), H2O (5 vol.%), SO2 (200 ppm), and the remainder was N2. The total gas flow rate was 500 mL / min, and the temperature was controlled at 120-240°C. The temperature was stabilized at 30°C for 30 minutes each. The NO concentration was measured using a flue gas analyzer. The denitrification efficiency of the catalyst was higher than 90% within the temperature range of 180-240°C, and there was no significant change in the denitrification efficiency after the catalyst was used at 180°C for 24 hours.

[0057] Comparative Example 1

[0058] (1) Catalyst preparation

[0059] Except that liquid nitrogen was not used for freezing during the catalyst preparation, other conditions were the same as those in Example 1;

[0060] (2) Catalytic activity test

[0061] Take 1mL of 20-40 mesh catalyst, pour it into a quartz tube with an inner diameter of 6mm, fix it with quartz wool and wire mesh, place the quartz tube in a tube furnace, and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake components: NO (500ppm), NH3 (500ppm), O2 (11vol.%), H2O (5vol.%), SO2 (200ppm), and the rest are N2. The total gas flow rate is 500mL / min, and the temperature is controlled at 120-240℃. Stay stable for 30 minutes every 30℃. Use a flue gas analyzer to measure the NO concentration. The denitrification efficiency of the catalyst at 180℃ is 42.8%, and the denitrification efficiency of the catalyst decreases significantly after using it at 180℃ for 24 hours.

[0062] (3) Contrast effect

[0063] Compared with Example 1, liquid nitrogen freezing is not used during the preparation of the catalyst. H2Ti4O9 will agglomerate during high-temperature calcination, resulting in the collapse of the layered structure, which in turn affects the microstructure of the catalyst, thereby losing the advantages of the catalyst's micron-layered structure, and ultimately leading to a significant decrease in activity and a significant decrease in anti-sulfur poisoning performance.

Claims

1. A micron layered rare earth-based denitration catalyst, characterized by: The catalyst uses micron-layered titanium dioxide as a carrier and a composite oxide of cerium oxide and copper oxide as an active component, and is prepared by a proton exchange freezing method-impregnation method. The mass percentage of the active component is 1 to 50% based on the mass of the carrier, and the mass ratio of cerium oxide to copper oxide in the active component is 1:(0.1 to 5).

2. The micron-layered rare earth-based denitration catalyst according to claim 1, characterized in that: Based on the mass of the carrier, the mass percentage of the active component is 5-30%, and the mass ratio of cerium oxide to copper oxide in the active component is 1:(0.1-1).

3. A method for preparing the catalyst according to claim 1, characterized in that: The preparation method of the catalyst is as follows: (1) Preparation of micron-layered titanium dioxide by proton exchange freezing method Preparation of layered K2Ti4O9 powder: titanium source and potassium source are mixed evenly, then placed in a microwave sintering furnace for microwave heating, and layered K2Ti4O9 powder is obtained after washing and drying; Preparation of slurry: Layered K2Ti4O9 powder and deionized water are mixed uniformly, and K2Ti4O9 colloid is obtained after ultrasonic dispersion. Nitric acid is then added and stirred continuously, and proton exchange is carried out. After filtration, H2Ti4O9 is obtained. H2Ti4O9, a binder, and deionized water are then mixed uniformly to obtain a slurry. Preparation of micron layered titanium dioxide: The slurry is first placed in liquid nitrogen and frozen for 30 to 60 minutes, then vacuum dried, and finally calcined at high temperature to obtain micron layered titanium dioxide; (2) Preparation of catalyst by impregnation method Weigh cerium salt, copper salt and deionized water and mix them evenly to prepare a precursor mixed solution, then place the micron layered titanium dioxide prepared in step (1) into the precursor mixed solution, vacuum dry and then calcine at high temperature to obtain a catalyst.

4. The preparation method according to claim 3, wherein: The preparation conditions of the layered K2Ti4O9 powder in step (1) are as follows: The titanium source is anatase titanium dioxide, the potassium source is potassium hydroxide, and the molar ratio of the titanium source to the potassium source is 1-3:1; the microwave heating power is 1.0-2.0 kW, the heating time is 2-4 hours; the drying temperature is 80-100° C., and the drying time is 4-8 hours.

5. The preparation method according to claim 3, wherein: The preparation conditions of step (1) slurry are as follows: The power of ultrasonic dispersion is 400-600W, and the time of ultrasonic dispersion is 4-6h; The concentration of nitric acid is 0.5 to 2 mol / L, the mass ratio of layered K2Ti4O9 powder to nitric acid is 1:(5 to 10), and the proton exchange time is 12 to 36 hours. The binder is chitosan, and the mass ratio of H2Ti4O9 to the binder is 1:(2-3).

6. The preparation method according to claim 3, wherein: The conditions for preparing micron-layered titanium dioxide in step (1) are as follows: vacuum drying temperature is 20-40° C., and vacuum drying time is 24-48 h; high-temperature calcination temperature is 400-600° C., and high-temperature calcination time is 4-8 h.

7. The preparation method according to claim 2, characterized in that: In step (2), the cerium salt is cerium nitrate hexahydrate or cerium chloride, and the copper salt is copper nitrate or copper chloride; The temperature of vacuum drying is 20-40° C., and the time of vacuum drying is 12-24 hours; the temperature of high-temperature roasting is 500-600° C., and the time of high-temperature roasting is 2-4 hours.

8. Use of the catalyst according to claim 1 in denitrification of complex flue gas in non-power industries.

9. The use according to claim 8, characterized in that Non-electric industries include steel sintering, dry cement and chemical industries.